Value Contextuality in Public Service Delivery. An Analysis of Street-Level Craftsmanship and Public–Private Partnerships. (3rd May 2020) - Paanakker, Hester; Reynaers, Anne-Marie
Abstract : This contribution questions the idea of value universalism and demonstrates that the actual meaning of good or ethical governance is context dependent—as are its constitutive values. To illustrate this point, Huberts' value framework on integrity and quality of governance is contrasted to two empirical case studies that demonstrate the contextuality of values in two specific settings of public service delivery: street-level craftsmanship and public–private partnerships (PPPs). Findings show that values do not work along the lines of the systematic frameworks public administration scholars come up with. They work along the lines of personal interpretative repertoires, and, on an aggregate level, along the lines of the confined and decisive professional logics of bounded policy domains.